PAIN AND DEPRESSION RISK AMONG ELDERLY PEOPLE LIVING IN A NURSING HOME - (:unkn) unknown (GUNES KITABEVI LTD STI, 2009)
Introduction: In this study was designed to investigate pain and depression status, relation between pain and depression, and influential factors in the elderly residing in a nursing home. Materials and Method: This investigation was performed in a nursing home that is linked to Social Services and Society for the Protection of Children between the dates October the 5th 2007 - December the 29th 2007 in Istanbul. The sample included 95 elderly who agreed to participate in interviews and who could be contacted to. Data were collected by a questionnaire, Numeric Pain Scale and Geriatric Depression Scale (GDS) during face-to-face interviews. Results: The prevalence of pain in old people that live in nursing home has determined as 57.9%. The prevalence of depression risk in old people is 66.3%. There is no statistically significant correlation between the severity of pain and the averages of depression risk scores (r=0.01; p=0.89). The average GDS scores of the elderly people who feel pain in whole day and who feel tingling pain have been determined higher than the others, and this is statistically significant (p<0.01). Conclusion: No statistically significant difference between presence of pain and average scores in GDS was determined (p>0.01).
Keywords: Depression; Pain; Pain Scale; Nursing Home; RESIDENTS; SYMPTOMS